The Effect of Loose Part Media on Fine Motor Skills of Children in Group B - Ella, Laela Rizki Fitriana; Sudaryanti (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The development of fine motor skills in early childhood is an important aspect that needs attention in the learning process. However, many students still experience difficulties in developing these skills, one of which is caused by the lack of creativity of educators in using varied and interesting learning media. As a result, more than 50% of children show suboptimal fine motor skills and minimal imagination in learning activities. Therefore, this study aims to determine the effect of loose part media on the fine motor skills of kindergarten students. This study uses a quantitative analysis method. The population and sample of this study were 52 kindergarten students. The sampling technique was based on the characteristics of the students with the same groups and numbers, so there were no specific criteria for determining the control and experimental classes. Data collection was carried out through observation and documentation using a research instrument that had undergone content validity and empirical validity tests. Meanwhile, reliability was tested using Cronbach's alpha formula. The data analysis technique used was quasi-experimental analysis. A quasi-experiment is an experiment in which the smallest experimental units are not randomly assigned to experimental and control groups (non-random assignment). The results of this study indicate that there is an effect on the fine motor skills of kindergarten students before and after the use of loose parts media. This can be seen from the results of the independent sample t-test, which yielded a tvalue of 3.619 and a Sig. value of 0.001 < 0.05. Based on the results of this study, recommendations will be made to schools to implement loose part media as a form of creativity for educators to train fine motor skills in children.